Empati Kultural pada Mahasiswa - Gustini, Neng (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2017)
Cultural empathy is the ability to feel what another person by an individual or a community group. Culture of others became the foundation behave in every interaction that exists. Empathy has the potential to transform differences into mutual understanding and deep understanding. Similarly, in guidance and counseling, a counselor absolutely have skills in counseling, one of which he must have a sense of empathy. Therefore, empathy is very important, both for educators and for counselors, especially for counselors, provide a sense of comfort to the counselee as if a counselor was feeling what counselees feel and recognize themselves in more depth. As for cultural empathy in counseling is very important for the counseling process is a process aid through the interaction between two individuals of different cultural backgrounds. One problem that often arises is the lack of empathy in communication that could lead to a misunderstanding in interaction. Whereas, the purpose of cultural empathy is to gather information and to establish a therapeutic alliance. This study aims to investigate and describe the cultural empathy in students. This study uses a quantitative approach with descriptive methods, instrument using a questionnaire and the sample was 83 students of UIN Sunan Gunung Jati Bandung. The findings of this research is cultural empathy of student UIN Sunan Gunung Jati Bandung categorized as being with an average by score of 83.84.